Mass loss from the progenitor of SN 1006? - Reynoso, Estela Marta (2008)
We have observed the remnant of SN 1006 with high resolution and sensitivity at 1.4 GHz. These data are combined with observations performed 11 years before to measure the expansion of the radio shell. The expansion parameter δ, defined as R ∝ t^{δ}, is found to be ˜ 0.62 for the brightest lobes. According to theoretical models, this value appears to be compatible with ejecta interacting with a circumstellar density profile decreasing as r^{-2}, characteristic of steady presupernova mass loss. However, this could not be the case if SN 1006 is still in the ejecta-dominated evolutionary stage.